Pelatihan Peningkatan PHBS dan Pengelolaan Air Siap Konsumsi pada Masyarakat Wilayah RW 006, Kelurahan Tanjung Duren Selatan - Halim, Johni; Louisa, Marie; Ariesanti, Yessy; Ayu Ratih Utari Mayun, I Gusti; Widhianingsih, Dhyani; Denilson (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
Water is crucial for human survival, serving both consumption needs and daily activities. However, water contamination often occurs when it is not managed and stored properly. Contaminated drinking water can pose health risks, causing various digestive diseases and even death, especially in children. Therefore, the management and storage of water require special attention. Indonesian communities, especially those in the RW 006, Tanjung Duren Selatan, are still limited in gathering clean water without proper water management for it to be made suitable for consumption. In response to this concern, a program was implemented to enhance awareness and empower the residents of RW 006, Tanjung Duren Selatan, focusing on improving environmental sanitation and the effective management of safe drinking water. The activities took place at the secretariat office of RW 006, Tanjung Duren Selatan, on Friday, November 10, 2023, from 08:30 to 10:15 AM. A total of 25 participants filled out attendance and completed pre-test questionnaires. Participants were then provided with education and training by the team on environmental sanitation, Community-Based Total Sanitation (STMB), proper management of household waste, and the handling of water intended for consumption. The post-test results showed an improvement in participants' knowledge and understanding regarding the enhancement of environmental sanitation and the management of water ready for consumption in households. It is hoped that participants will serve as links in communication and educators within the local community, ultimately contributing to improved sanitation and an enhanced quality of life.